1987
DOI: 10.1016/s0886-3350(87)80068-8
|View full text |Cite
|
Sign up to set email alerts
|

Morphometric analysis of corneal endothelium following radial keratotomy

Abstract: We performed morphometric analysis of the central corneal endothelium on 24 eyes of 19 patients who had had anterior radial keratotomy. The endothelium was analyzed for a variety of parameters, including cell area, perimeter, side lengths, cell shape, and number of sides. Mean, standard deviation, and coefficient of variation were calculated for each parameter. The mean cell density decreased from 2,835 to 2,677 cells/mm2, mean cell perimeter increased from 71.4 micron to 74.3 micron, and mean side length incr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
7
0
1

Year Published

1988
1988
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(9 citation statements)
references
References 15 publications
1
7
0
1
Order By: Relevance
“…Specular microscopy had previously docu mented endothelial cell loss of between 5% and 8%. 17,18 This is in line with other stud ies1 9 ,20 and its measurement had been discon tinued prior to this series.…”
Section: Complicationssupporting
confidence: 89%
See 1 more Smart Citation
“…Specular microscopy had previously docu mented endothelial cell loss of between 5% and 8%. 17,18 This is in line with other stud ies1 9 ,20 and its measurement had been discon tinued prior to this series.…”
Section: Complicationssupporting
confidence: 89%
“…(16) Guttae Gentamycin and Guttae Cyclogyl 1 % were instilled in the operated eyes. (17) The eye was lightly patched for three hours only. (18) Post-operative pain was controlled with tablets OF118 for 12 to 18 hours only.…”
Section: Technique Of Radial Keratotomymentioning
confidence: 99%
“…Although endothelial loss has been reported after RK,6,7 some studies suggest that the rate of endothelial loss stabilizes over time 8,9. We report seven cases (13 eyes) with a previous history of RK presenting with various degrees of guttata and endothelial dysfunction.…”
Section: Introductionmentioning
confidence: 77%
“…Ten years after surgery, 60 of 80 eyes developed bullous keratopathy 7. Chiba et al reported a post-RK endothelial cell loss of 14.1% with significant pleomorphism associated with microperforation and a smaller central clear zone of treatment, 6 to 30 months after surgery 6. In animal models, no difference between the reported 14%–15% endothelial cell loss was seen in eight versus 16 incision RK at 6 months 10…”
Section: Discussionmentioning
confidence: 99%
“…По данным разных авторов степень потери эндоте-лиальных клеток в период от 1 месяца до 7 лет после ПРК составляет от 3 до 10% [7,10,11]. На степень сни-жения плотности эндотелия влияет количество над-резов, маленький диаметр центральной оптической зоны вне рубцов, грубые манипуляции на роговице кератотомическим ножом с «тупым» металлическим лезвием, применение больших усилий во время вы-полнения надрезов с прогибанием участков роговицы, длительность послеоперационной воспалительной ре-акции.…”
unclassified